2010
DOI: 10.1007/s00167-010-1337-4
|View full text |Cite
|
Sign up to set email alerts
|

Autologous matrix-induced chondrogenesis combined with platelet-rich plasma gel: technical description and a five pilot patients report

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
145
1
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(157 citation statements)
references
References 36 publications
7
145
1
4
Order By: Relevance
“…He had IKDC, Tegner-Lysholm, and Lysholm-Gillquist scores of 82. 8,5, and 74 at 2-year followup compared with 5.75, 0, and 11 at surgery, respectively. On MRI, hypertrophy of the periosteum conforming to joint congruity was observed as early as at the 6-month followup (Fig.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…He had IKDC, Tegner-Lysholm, and Lysholm-Gillquist scores of 82. 8,5, and 74 at 2-year followup compared with 5.75, 0, and 11 at surgery, respectively. On MRI, hypertrophy of the periosteum conforming to joint congruity was observed as early as at the 6-month followup (Fig.…”
Section: Resultsmentioning
confidence: 88%
“…Newer cell-based therapies including BMSCs have been suggested by various authors as a result of its superior proliferation rate and differentiation capacity [3,16,21]. Autologous matrix-induced chondrogenesis techniques combining the use of microfracture with matrix-based techniques using a collagen membrane to serve as a scaffold are increasingly studied for its potential to allow effective reconstruction of large fragments of a damaged cartilage surface without the need for a second intervention and complex laboratory preparation [8]. It would be interesting for future studies to compare the various cell-based therapy techniques based on the clinical and functional improvement seen in patients.…”
Section: Discussionmentioning
confidence: 99%
“…PRP has been used in trauma and orthopaedic surgery [1,27,30] because it is an autologous source of various growth factors [21]. Injection of PRP in 115 knees with chronic degenerative symptoms reduced pain and improved knee function and quality of life in younger patients as assessed by International Knee Documentation Committee (IKDC) score and visual analog scale (VAS) score at 1 and 2 years of followup [6,17]. One study suggested the importance of keeping PRP-derived growth factors and cytokines in the wound site and slowly releasing them as the wound site becomes infiltrated with repair cells [9].…”
Section: Introductionmentioning
confidence: 99%
“…In a study of 20 patients with osteochondral lesions, PRP combined with a hyaluronan scaffold induced cartilaginous tissue regeneration and improved functional scores (IKDC and KOOS) at 2 years followup [4]. For chondral patellar defects, a pilot study reported five patients who had a PRP gel used to fill microfractured cartilage defects covered with a porcine type I/III collagen membrane [6]. Patients improved in VAS pain score and KOOS, however, MRI showed three of the five patients had incomplete filling [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation